Using Mobile Technologies in Education: A New Pedagogical Approach to Promote Reading Literacy - Marques, C. G. (2021)
The acquisition of reading skills is decisive for the academic achievement of students. However, learning to read is a complex process. With this in mind, several attempts have been made to find new educational approaches to enhance students' reading motivation. Considering the enormous potential of ICT for education and training, we have developed a digital repository of teaching and learning materials and a multiplatform application that runs on mobile devices: Letrinhas. This information system was designed to promote the development of reading and to provide tools for monitoring and assessing reading skills against the curricular targets set by the Ministry of Education. Letrinhas was evaluated by specialists and users and a high level of satisfaction was observed among students and teachers as time and effort spent to consolidate reading is considerably reduced with this application. This evaluation also enabled to identify features that will be available in the future.